Stability of omeprazole in a commercial calcium carbonate based oral suspension at 2, 5 and 10 mg/mL stored under refrigeration (4°C) for 70 days. (21st February 2022) - Low, Mitchell; Singh, Simi; Venkataya, Beatrice; Pearson, Jarryd; Ibrahim, Martha; Jarouche, Mariam; Khoo, Cheang; Rowe, James; Li, Chun G.
Abstract: Background: Omeprazole is a commonly prescribed proton pump inhibitor that acts to reduce gastric acid secretion. Liquid suspensions are preferred for paediatrics or patients with difficulty swallowing, however, are unstable. Aim: This study reports on the stability of USP‐grade omeprazole, raw powder at 2, 5 and 10 mg/mL dosages suspended in Oral Mix Dry Alka SF (OMSF) stored at 4°C for 70 days. Method: The omeprazole concentration in the suspensions were determined at the time of preparation and at 7, 14, 28, 42, 56 and 70 days by high performance liquid chromatography with photodiode array detection (HPLC‐PDA). The pH, homogeneity, colour, odour, and microbial levels were also determined. Results: All the preparations are stable at 4°C for 70 days, with omeprazole concentration remaining within ±10% of the initial concentration. The pH showed a gradual decline from 9.0 to 7.7 over the study which is an acceptable change. The preparations passed microbial testing up to 70 days. Conclusion: The 70 days stability achieved in OMSF far exceeds the 28 day beyond‐use‐date recommended by the Australian Pharmaceutical Formulary. The OMSF base provides compounding pharmacists with a convenient method to prepare omeprazole suspensions over a wide range of concentrations with extended dating, providing added convenience for the consumer and pharmacists.